Cases on open-linked data and semantic web applications - Ordóñez de Pablos, Patricia, 1975- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book brings together new theories, research findings and case studies that cover the recent developments and approaches toward applied open linked data and semantic web in the context of information systems"--Provided by publisher.